Identification of implementation and understanding of health and work safety with hazard and operability study (Hazop) method at SMG Mulya Factory - Tri Wisudawati; Wahyu Adhi Saputro (Jurnal Teknika, 2021)
The micro, small and medium enterprises sector has a major contribution to economic development in Indonesia. One of the micro, small, and medium enterprises (UMKM) is the SMG Mulya Factory, which produces snacks, and complimentary crackers. The work area certainly has risks and hazards that may arise. The reason makes MSME owners implement occupational safety and health for both owners and workers. This study aims to identify the application and understanding of occupational health and safety at the SMG Mulya Factory. This research uses the hazard and operability study (HAZOP) method. The results showed that the potential for extreme work hazards was 8.33%, high and medium risk hazards were 25%, and low risk was 41.83%. There is an extreme risk when frying crackers is not accompanied by personal protective equipment (PPE), so it is feared that it will be splashed by heat from the oil used when frying. There is a high risk when the dough-making machine does not use a lid, so it is feared that when washing the tool, there will be puddles of water on the floor so that it is slippery and causes injuries to workers. Sektor usaha mikro, kecil dan menengah memiliki kontribusi yang besar dalam pembangunan ekonomi di Indonesia. Salah satu pengembangan Unit Usaha Mikro kecil dan Menengah (UMKM) adalah adanya Pabrik SMG Mulya yang memproduksi krupuk yang notabenenya adalah makanan ringan, cemilan dan pelengkap. Area kerja tentunya memiliki resiko dan bahaya yang dimungkinkan muncul. Hal tersebut membuat pemilik UMKM menerapkan adanya keselamatan dan kesehatan kerja baik bagi pemilik maupun bagi pekerja. Penelitian ini bertujuan untuk mengidentifikasi penerapan dan pemahaman kesehatan dan keselamatan kerja pada Pabrik SMG Mulya. Penelitian ini menggunakan metode hazard and operability study (HAZOP). Hasil penelitian dapat menunjukkan bahwa potensi bahaya kerja ekstrim sebesar 8,33%, potensi bahaya risiko tinggi dan sedang sebesar 25% dan risiko rendah sebesar 41,83%. Resiko ekstrim terdapat pada saat penggorengan krupuk tidak disertai penggunaan alat pelindung diri (APD) sehingga dikhawatirkan terkena cipratan panas dari minyak yang digunakan saat penggorengan. Resiko tinggi terdapat pada saat pembuatan adonan mesin tidak menggunakan tutup sehingga dikhawatirkan ketika mencuci alat tersebut menjadikan adanya genangan air pada lantai sehingga licin dan mengakibatkan luka pada pekerja.